Potensi Deforestasi di Pulau Kalimantan: Pro dan Kontra Migrasi - Berlianty, Tryanita; Meiliana, Trinita (HK-Publishing, 2023)
Abstract The development of IKN emerged an environmental issues which have now become one of the main concerns of Indonesian citizens, many predictions of IKN have the potential for environmental aspects. The surge in migrants on the island of Kalimantan is also included in the issue of environmental concerns that will disrupt and even damage the preservation of nature in Kalimantan, so that the existence of forest migrants reaps the pros and cons of the community which is considered to give rise to the potential for deforestation. So this research tries to analyze with the theory of Libertarian thought and Capitalism. Libertarian thinking is used to analyze the perspective of society that is pro towards the existence of migrants, while Capitalism's thinking is used to analyze the perspective of the state which is used as an investor for business capital. so that the results obtained can bring out various potentials generated from each perspective.Keywords: Business capital, migration, relocation of the national capital. AbstrakPembangunan IKN melahirkan isu lingkungan yang kini menjadi salah satu perhatian utama warga Indonesia, banyak prediksi IKN yang berpotensi pada aspek lingkungan. Lonjakan migran di Pulau Kalimantan juga termasuk kedalam isu lingkungan kekhawatiran yang akan mengganggu bahkan merusak kelestarian hutan alam di Kalimantan, sehingga keberadaan migran menuai pro dan kontra masyarakat yang dianggap akan melahirkan potensi deforestrasi. Maka penelitian ini mencoba untuk menganalisa dengan teori pemikiran Libertarian dan Kapitalisme. Pemikiran Libertarian digunakan untuk mengalisis perspektif masyarakat yang pro terhadap keberadaan migran, sedangkan pemikiran Kapitalisme digunakan untuk menganalisis perspektif negara yang dijadikan sebagai ladang modal usaha investor. sehingga hasil yang diperoleh dapat memunculkan berbagai potensi yang dihasilkan dari masing-masing perspektif.Kata Kunci: Modal usaha, migrasi, Pemindahan Ibu Kota Negara